Regularity estimates for nonlinear elliptic measure data problems with nonstandard growth. (May 2019) - Byun, Sun-Sig; Liang, Shuang; Youn, Yeonghun
Abstract: We prove a global Calderón–Zygmund type estimate for the gradient of a solution to a nonlinear elliptic problem with nonstandard growth when the right-hand side is a bounded Radon measure. Minimal regularity requirements on both the nonlinearity and the boundary of the domain are investigated for such a gradient estimate.